Hallux rigidus: clinical examination, radiology, and classification - Arrondo, Guillermo Martin; Casola, Leandro (Journal of the Foot & Ankle, 2021)
The severity of hallux rigidus depends on the degree of joint involvement, from local pain to stress fractures of other bones of the foot due to hyper-support. Radiology is mandatory to have an accurate diagnosis and gives us a parameter of joint injury. We use the Coughlin and Shurnas classification as the gold standard for treatment. Level of Evidence IV.